Interpretation and performance:An investigation into Franz Scuberts Piano Sonata in A Major D959 - Horng, Kent Tham (Tanjong Malim, 2016)
Interpretation and performance:An investigation into Franz Scuberts Piano Sonata in A Major D959 by Horng, Kent Tham